Biosynthesis of colabomycin E, a new manumycin-family metabolite, involves an unusual chain-length factor - Petříčková, Kateřina; Pospíšil, Stanislav; Kuzma, Marek; Tylová, Tereza; Jágr, Michal; Tomek, Petr; Chroňáková, Alica; Brabcová, Eva; Anděra, Ladislav; Krištůfek, Václav; Petříček, Miroslav (Chembiochem, 2014)
Colabomycin E is a new member of the manumycin-type metabolites produced by the strain Streptomyces aureus SOK1/5-04 and identified by genetic screening from a library of streptomycete strains. The structures of colabomycin E and accompanying congeners were resolved. The entire biosynthetic gene cluster was cloned and expressed in Streptomyces lividans. Bioinformatic analysis and mutagenic studies identified components of the biosynthetic pathway that are involved in the formation of both polyketide chains. Recombinant polyketide synthases (PKSs) assembled from the components of colabomycin E and asukamycin biosynthetic routes catalyzing the biosynthesis of "lower" carbon chains were constructed and expressed in S. aureus SOK1/5-04 ΔcolC11-14 deletion mutant. Analysis of the metabolites produced by recombinant strains provided evidence that in both biosynthetic pathways the length of the lower carbon chain is controlled by an unusual chain-length factor supporting biosynthesis either of a triketide in asukamycin or of a tetraketide in colabomycin E. Biological activity assays indicated that colabomycin E significantly inhibited IL-1β release from THP-1 cells and might thus potentially act as an anti-inflammatory agent.
Keywords: polyketides; Bridged Bicyclo Compounds, Heterocyclic; biosynthesis; bicyklické sloučeniny heterocyklické; Interleukin-1beta; chain-length factors; Humans; antiflogistika; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; polynenasycené alkamidy; manumycins; Dose-Response Relationship, Drug; secondary metabolites; lidé; molekulární struktura; Molecular Structure; buněčné linie; Cell Line; interleukin-1beta; Anti-Inflammatory Agents; vztah mezi dávkou a účinkem léčiva; Polyunsaturated Alkamides; Streptomyces